Pendidikan Karakter Pada Kartun Nussa dan Rara - Firdasari, Annisa Nurul; Salma, Faizah Nabila; Rozaen, Ghazzio Ridhoathallah; Galih, Nenden Endah Wening; Nursopiah, Nursopiah; Supriyono, Supriyono (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Kartun